THE HISTORY OF THE DEVELOPMENT OF LEGISLATION IN INDONESIA AND ITS INFLUENCE ON SHARIA ECONOMIC LAW - Riska Pebriani; Gina Raudatul Jannah; Zaitun; Bunga Juniarti Syahputri; Nurmala; Silpi Nadia Sari; Aulia; Rassya Aulia Rahmadani; Iinata Istahuna Putri; Nurlaila; Erza Lianti; Sizo Karlita (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the historical development of legislation in Indonesia and its influence on the growth of Islamic economic law. The research employed a normative legal approach using qualitative library research. Data were collected from legislation, legal documents, academic books, and scientific journals, then analyzed descriptively. The findings indicate that Indonesian legislation has evolved from the colonial period to the reform era, significantly shaping the national legal system. These legal developments have encouraged the establishment of various regulations governing Islamic economic activities, providing greater legal certainty for Islamic financial institutions and business actors. Therefore, continuous legislative reform plays a crucial role in strengthening the implementation and development of Islamic economic law in Indonesia.